FROM MAIN COMPONENT TO EQUAL CITIZEN: RECONSTRUCTION OF THE JA’FARI IDENTITY IN TURKEY - Erdogan, Baris (European Scientific Journal, ESJ, 2015)
The ethnic, sectarian, and political conflicts in Iraq and Syria serve as significant catalysts for Turkey’s Ja’faris to redefine their social identity. This article comprises a sociological analysis of the Ja’fari community who are predominantly Azeri Turks adhering to the Shiite sect. The article addresses the parameters they pursue in order to construct and position their own social identity in light of the developments in foreign and domestic politics in Turkey where the Sunni population constitutes the quantitative and political majority. Since the foundation of the secular Republic up until today, the establishment has pursued the policy of homogenizing citizens via its ideological apparatus based on Sunni Islam references. As a response, Ja’faris have been rebuilding their identity in tandem with the social changes. In order to integrate with the national policies and overcome the barriers that arise from sectarian differences, Ja’faris constantly underscore in the public sphere that they are the founding components of the nation as “Turks” and “Muslim”s. However, Turkey’s foreign and domestic politics during the conflicts in Iraq, and particularly in the post-Syrian crisis has engendered, citing the Ja’fari leader’s own words, a “shocking effect” within the Ja’fari community. Given the new state of affairs, Ja’faris are rebuilding the Ja’fari identity using a dual language: On one hand, they continue to highlight the “superior” Turkish and Muslim identity that is embraced by the unofficial state ideology, and on the other hand, they embark on a quest for a more civilian equal citizenship within social movements.